Postpartum and Newborn Care in the Karo Ethnic - Debora Paninsari; Chrismis Novalinda; Tiarnida Nababan (Indonesian Journal of Global Health Research, 2025)
Traditional medicine is still an important part of Karo people's lives and is still believed in today, especially in postpartum care for mothers. The herbs used are generally based on local plants. This practice not only functions medically according to local beliefs. Kuning Las, Tawar, massage oil, Sembur, and Oukup or steam bath, spray, and Sira lada porridge.But also has cultural and spiritual values that strengthen social ties and family support during the postpartum period. This study was conducted to determine the Karo Tribe's Traditions in Caring for Postpartum Mothers and Newborns Method: This study uses a quantitative research approach with a cross-sectional design.. Data were collected using a structured questionnaire and analyzed statistically to see the relationship between dependent and independent variables. This study was conducted in Pancur Batu District, North Sumatra. The reason for choosing this area as a research location is because the area includes the Batak Karo ethnic community. The population in this study were postpartum mothers and newborns in Pancur Batu District. The sample in this study is part of the population used as a research object that meets the inclusion criteria and exclusion criteria totaling 50 people. The data was obtained through questionnaires and interviews, then the data was subjected to univariate and bivariate analysis. Conclusions: Postpartum and newborn care for Karo people includes several treatments, oukup, kuning las, tawar (karo herbal medicine), sembur and sira lada porridge. The benefits of the treatment itself can be to make the mother healthier and stronger, to prevent the mother from catching a cold. In infants, the use of param on the crown so that the baby's head hardens quickly, sira lada porridge as one of the treatments to facilitate breast milk.